Islamic Word of Mouth: The Role of Da'wah and Community in Promoting Islamic Educational Institutions - Nurhidayati (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
One promotional approach that has proven effective and cost-effective is the Word of Mouth (WOM) strategy, namely the dissemination of information or experiences from one individual to another, verbally or digitally. Institutions need to have a mechanism for clarification, media literacy, and Islamic communication education so that the spread of WOM remains ethical and truthful. The results of the study are that Word of Mouth (WOM) is a very effective communication strategy in promoting Islamic educational institutions. However, from an Islamic perspective, WOM is not merely a promotional tool, but also a medium for da'wah that conveys the truth, spreads goodness, and strengthens the image of the institution ethically and spiritually. The implementation of Islamic Word of Mouth requires the involvement of all stakeholders, especially internal communities such as teachers, parents of students, alumni, and local community leaders. The role of this community is the main force in creating authentic, memorable, and sustainable promotions. The practice of Islamic WOM must be based on the values of da'wah, namely conveying correct information, not exaggerating, not containing slander, and always prioritizing etiquette. Promotion based on positive experiences and role models is far more effective than formal advertising because it has deep emotional and spiritual power.